Punching tool wear modeling using finite element method - Melcot, Jinikol (2009)
This paper will investigate the factor or parameter that will effect the wear that occur in the punching tool. The punching tool will be redesign by change the shear angle, do the simulation with diferrent force applied to the punching tool by using finite element method and also change the thickness of the punching tool. The purpose of this paper is to investigate the wear that will occur in the punching tool in order to increase the tool life and in the same time will increase the quantity and quality production in the factory. Using finite element method, the parameter of the cause and parameter of the wear in tool will investigate.